Experimental investigation of tool wear TiAlN(Al2O3)/TiN-coated carbide in the cam-shaft turning process - arfan halim (Politeknik Negeri Lhokseumawe, 2022)
This research carried out experimental tests to determine the tool life and wear of Titanium Aluminum Nitride and Titanium Nitride-coated carbide tools (TiAlN/Al2O3 TiN) during the hard facing process of cam shaft material turning. The results of this study will be used as a parameter for selecting carbide cutting tools in Teaching Factory (TEFA) activities. In the cutting process, the parameters used are VC = 36,74 m/min, f = 0,52 mm/rev, a = 0,2 mm, t = 460 min; and the cutting conditions are wet turning. The results showed that the TiAlN/ Al2O3-coated carbide tool experienced tool wear at the 100th minute with a VB value of 0,33 mm, while the TiN-coated carbide tool experienced tool wear at the 200th minute with a VB value of 0,30 mm. Theoretically, tool life for turning process conditions was analysed by graphical method in order to obtain the Taylor equation for TiAlN/Al2O3 coated carbide tools with an exponent value of n = 0,8 and a CT constant = 1.462,65 so that the Taylor tool life equation is V.Tn = CT ↔ V.T0,8 = 1.462,65. The results of the TiN carbide tool life test showed that the exponent n = 0,6 and CT constant = 882,59 so that the Taylor tool life equation is V.Tn = CT ↔ V.T0,6 = 882,59. Failure of TiAlN/Al2O3 and TiN-coated carbide tools on hard-processed cam shaft material cutting to face edge wear (VB), crater wear (KA), peeling of the tool material layer, and formation of built-up edge (BUE). The experimental test results of TiAlN/Al2O3 and TiN-coated carbide tools on the cutting of cam shaft material using a hard facing process show TiN carbide tools have a longer tool life than TiAlN/Al2O3, so they are recommended for Teaching Factory (TEFA) activities at Simas Berau Polytechnic